The Evolution of One Health concept – A European perspective - Mełgieś, Katarzyna Małgorzata (Review of European and Comparative Law, 2024)
Over the past years, the European Union has been engaged in activities aimed at finding solutions to protect health in accordance with interdisciplinary and transdisciplinary thinking in line with the One Health approach. The experiences related to the Covid-19 pandemic, clearly demonstrated the close connection between humans, animals, and the shared environment and increased interest for this approach to be applied and translated into action. This paper seeks to present the readiness of the European Union and its institutions for the challenges related to the political and legal approach and implementation of One Health concept.